DESAIN UNTUK MENINGKATKAN KUALITAS HIDUP MELALUI STRATEGI “DESIGN FOR HAPPINESS”: KONSEP DAN APLIKASI DI UI UX - Devanny Gumulya (Tanra: Jurnal Desain Komunikasi Visual Fakultas Seni Dan Desain Universitas Negeri Makassar, 2026)
Many individuals strive for a high quality of life, which is why the "Design for Happiness" (Dfh) strategy has been developed as a means of creating design solutions that offer positive experiences and promote happiness among users. This concept is commonly applied in smartphone app design, as the digital nature of applications enables extensive scalability. However, there are still many UI UX designers who lack a thorough comprehension of the Dfh concept and design process. Consequently, this research delves into the application of the "Design for Happiness" (Dfh) concept to enhance the quality of life through the design of digital products. The study utilizes the "research through design" methodology to formulate a framework for the digital product design process employing the Dfh concept, which encompasses four steps. The initial step is to identify user needs in four Dfh components, namely talents and skills, pleasures, personal values, and contributions to others. The subsequent step is to comprehend user needs, generate ideas by exploring multiple solution concepts by combining different user feedbacks, and design the user experience. The research's implication lies in its ability to provide practical guidance for product designers in creating digital products that boost users' quality of life. This research can also help expand product designers' understanding of the Dfh concept.